Transitions from Casual Employment in Australia - Wooden, M; Buddelmeyer, H (My University, 2008)
A distinctive feature of the Australian labour market is a high incidence of casual employment. Almost 27 percent of Australian employees in 2006 were classified as employed on a casual basis, an alarmingly high proportion given the strong claims often made about the harmful effects that casual employment can have on future employment prospects. But are such claims justified? This paper uses longitudinal data from the HILDA Survey to examine the extent to which casual employees are able to access non-casual jobs in the future and to contrast the experiences of casual employees with that of other labour market participants. A dynamic MNL model of labour market states is estimated which reveals high annual rates of mobility from casual employment into non-casual employment. Further, among men, casual employees are found to be far more likely to make the transition into non-casual employment than otherwise comparable unemployed job seekers. For women, however, this is not the case.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Melbourne Institute Working Papers
Keywords: Employment; Employment -- Labour force status and attachment; Labour market; Employment and unemployment